2010
DOI: 10.1007/s10552-010-9654-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of adenomas in individuals with a family history of colorectal cancer: results of a meta-analysis

Abstract: Individuals with a family history of colorectal cancer have a considerably higher prevalence of adenomas compared to individuals without a family history. This is consistent with their increased risk of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
(53 reference statements)
3
19
0
2
Order By: Relevance
“…Our results confirm the increased risk of CRCs associated with FHCC in first-degree relatives, although only in women with no colonoscopy screening [25]. Those with previous colonoscopy had a similar risk to those with no FHCC, as already reported [7,30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results confirm the increased risk of CRCs associated with FHCC in first-degree relatives, although only in women with no colonoscopy screening [25]. Those with previous colonoscopy had a similar risk to those with no FHCC, as already reported [7,30].…”
Section: Discussionsupporting
confidence: 90%
“…However, analyses stratified on year 2002, which could account for progress in endoscopic techniques, led to similar results in the two periods. New techniques such as virtual chromoendoscopy are being developed to improve detection of flat lesions [25]. In addition, tumors of the proximal colon more often develop from serrated adenomas which often harbor-specific features, such as microsatellite instability, BRAF mutations, or high gene methylation as compared with distal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In our study advanced adenomas were found in a minority (2.8%) of the population, predominantly in the age group ‡ 60 years, but these findings are comparable to Lin's study which had a mean age most similar to ours (Table V). It is a well-established fact that increased age is positively correlated with a higher prevalence of adenomas [18], which also was shown in the present study; in those > 60 years old 20% had adenomas compared to 5% in the cohort < 60.…”
Section: Discussionsupporting
confidence: 89%
“…3 Similarly, a meta-analysis that included 13 studies found an increased risk of colorectal adenomas in individuals with a family history of CRC (OR 1.7; 95% CI 1.4---3.5). 15 Regarding CRC location, FDRs of patients with colon cancer have a higher risk of CRC than those with relatives whose tumors are located in the rectum (RR ≈ 2.3 vs. ≈1.9). FDRs of patients with left-sided colon cancer are at greater risk than those of patients with right-sided tumors.…”
Section: Familial Risk Of Colorectal Cancermentioning
confidence: 98%